Uveitis in paediatric Behçet disease: a large multicentric Italian cohort - Ilaria Maccora; Sara Immacolata Orsini; Romina Gallizzi; Davide Montin; Marco Cattalini; Francesco La Torre; Alessandra Spagnolo; Federico Diomeda; Gabriele Simonini (Therapeutic Advances in Musculoskeletal Disease)
Background: Behçet disease (BD) is a rare disease in childhood and its uveitis may lead to blindness if not properly treated. Objectives: We aim to describe a cohort of paediatric BD patients with uveitis. Design: This is a multicentric retrospective study. Methods: Six paediatric rheumatology units in Italy were involved including children with a diagnosis of paediatric BD according to the International Criteria for BD Criteria and/or to the International Study Group Criteria for BD, or Paediatric BD classification criteria if they had uveitis. Demographic, laboratory and clinical data were collected and followed up to March 2023. Ocular characteristics and treatment response were assessed according to Standardization Uveitis Nomenclature. Results: Among the 97 children with BD followed, 33 (34%) had uveitis (22 males, 66.7%). The median age at onset of BD and uveitis were, respectively, 11.5 years (2.5–17.1) and 11 years (3–17.3). Uveitis preceded BD diagnosis in 18 children (54.5%). Seventeen children had HLA B51 positivity (51.5%). Uveitis was bilateral in 25 (75.8%), and panuveitis in 16 (48.5%). All the patients received at least 1 systemic treatment for uveitis: 25 adalimumab, 2 tocilizumab, 1 abatacept, 3 infliximab, 4 azathioprine, 1 methotrexate and 1 corticosteroid. The remission was achieved with 30/35 treatments (85.7%) after a median time of 8 months (6–24). Six children had a relapse in therapy after the achievement of remission (20%). Fourteen patients stopped the therapy for persistent remission, but 5 relapsed (35.7%) after a median time of 9 months (range 1–48). Conclusion: Uveitis in BD is a sight-threatening condition, and it is more frequently a panuveitis. Biologic treatments seem to be often required to control ocular inflammation.